(untitled) (Proceeding of SINERGY, 2026)
This study explores the innovation process and product development strategies implemented by a small-scale geospatial technology company led by young professionals, focusing on two flagship digital products, namely the .GIS platform for digital map creation and Weather Targeting Automation (WTA). The analysis in this study employs the Open/Closed Innovation framework to examine how the innovation process takes place within the company. In addition, the author also applies the Market Pull and Technology Push frameworks to analyze the company’s geospatial-based product development strategies. As a result of the analysis of the innovation process, the company demonstrates a relatively complex innovation process, as although technology development is carried out independently by the internal team, the .GIS platform product can only be utilized by end users after entering the co-creation stage. The development process of technological products is also conducted through a combination of market pull and technology push strategies, indicating that the integration of these two product development strategies is feasible for the company.